Pengaruh Penggunaan Lumio By Smart Terhadap Hasil Belajar Siswa Pada Materi Analisis Data - Stevvi Clara Adinda; Dewi Sulistiyarini; Febrianto Sabirin (LPD Universitas PGRI Pontianak, 2026)
Abstract: This study aims to determine the effect of using the Lumio by SMART interactive learning media on the learning outcomes of tenth-grade students at SMA Negeri 1 Ngabang on the Data Analysis material. The research employed a quantitative approach with a quasi-experimental method using a Non-Equivalent Control Group Design. The sample consisted of 60 students, divided into an experimental group of 30 students who were taught using Lumio by SMART, and a control group of 30 students who were taught using conventional learning media. Data were collected using multiple-choice and performance tests administered as pre-tests and post-tests. The results of the descriptive analysis showed that the experimental group's average score increased significantly from 52.80 in the pre-test to 78.06 in the post-test, while the control group's average score increased from 50.27 to 68.62. Furthermore, the initial abilities of both groups were equivalent before the treatment, as indicated by the pre-test significance value of 0.505. After the intervention, the Independent Sample t-test on the post-test data yielded a significance value of 0.009, which is less than 0.05. This result indicates that the null hypothesis is rejected and the alternative hypothesis is accepted. Therefore, it can be concluded that there is a significant difference in learning outcomes, proving that the use of Lumio by SMART interactive learning media provides a positive and significant effect on improving student learning outcomes in the Data Analysis material compared to conventional media. Keywords: Lumio by SMART, Learning Outcomes, Data Analysis, Informatics, Quasi-Experiment